Effect of Chemotherapy on Quality of Life of Lung Cancer Patients: Scoping Review - Novita Andayani; Suryawati suryawati; Nadya Salsabila; Desi Salwani; Hendra Kurniawan (Indonesian Society of Respirology (ISR), 2022)
Background: Lung cancer is a tumor originating from the lung parenchyma or in the bronchi. Lung cancer is the second most frequently diagnosed cancer. The treatment often used is chemotherapy as most lung cancers are diagnosed late. Chemotherapy can provide many benefits but also has side effects because it works by killing healthy replicating cells. Symptoms of cancer that appear as well as side effects of therapy have an impact on the patient's quality of life. Quality of life is a person's perception of his position in life in the context of values ​​and culture. Quality of life can determine a person's general well-being and well-being is the main goal of treatment. This study aims to determine the effect of chemotherapy on the quality of life of lung cancer patients. Method: This Scoping Review was compiled by conducting a literature search on the PubMed, ScienceDirect, SpringerLink databases, and manual searches on Google Scholar with the keywords “Lung Cancer” AND “Chemotherapy” AND “Quality of Life” from 2016 to 2021 publication period. Scoping This review is guided by the PRISMA-ScR checklist. Results: As much as 30 journals were obtained based on inclusion and exclusion criteria from this process. We found that most of the literature states that chemotherapy has a positive effect in improving the quality of life of lung cancer patients, which are dominated by advanced NSCLC cancer types. Conclusion: Aspects that can affect the quality of life of lung cancer patients undergoing chemotherapy are the available health facilities, the choice of chemotherapy regimen, the timing of the quality-of-life assessment, and the patient's socio-cultural background.